2022
DOI: 10.3390/su14116771
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corporate Social Responsibility on Consumer Purchase Intention: The Mediating Role of Consumer Engagement via Social Media

Abstract: Corporate Social Responsibility (CSR) has become a vital factor in how organizations run their businesses. Consumers are becoming more aware of it and are expecting it from organizations. With the rise of social media, organizations have another channel to communicate their CSR activities to their stakeholders. A good deal of research has been conducted on CSR and its relation to consumers. However, there is limited research on its influence on consumers via social media channels. Therefore, this research stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…This supports previous research evidence on social responsibility and consumer intent to protect the environment during the COVID-19 pandemic [ 1 , 108 ]. Furthermore, there are studies [ 123 ] that point to the commitment of consumers toward the activities of corporate social responsibility of companies (CSR) and how this contributes to their purchase intention. That is, consumers’ growing concern for the environment puts pressure on organizations to be environmentally responsible [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…This supports previous research evidence on social responsibility and consumer intent to protect the environment during the COVID-19 pandemic [ 1 , 108 ]. Furthermore, there are studies [ 123 ] that point to the commitment of consumers toward the activities of corporate social responsibility of companies (CSR) and how this contributes to their purchase intention. That is, consumers’ growing concern for the environment puts pressure on organizations to be environmentally responsible [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Fischbein and Ajzen (1975) theory of planned behavior, theory of reasoned actions, argue that comprehending the conditions of human conduct in extents terms of diverse elements may be crucial for organizations. Some recent studies have shown the relationships between CSR and consumers by taking consumers as important stakeholders ( Al-Haddad et al, 2022 ; Rynerzewska and Hetrick, 2022 ; Waheed et al, 2020a , Waheed et al, 2020b ; Waheed et al, 2020a , Waheed et al, 2020b ). A recent study of Rynerzewska and Hetrick (2022) examined the connection between CSR and consumer boycotts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A study of Zarei and Mirzaei (2022) attempted to uncover the relationships of CSR with respect to consumers' green perception. A recent study revealed the relationships of CSR in terms of consumer GPI ( Al-Haddad et al, 2022 ). A well-known study of Wu and Zhu (2021) researched the area of customers' behavioral intention as well as customers’ identifications during the era of Covid-19.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, engagement has been found to mediate the relationship between technology adoption and intention (Saputro and Hidayat, 2020;Abrar, 2018). Similarly, the positive and significant mediating effect of consumer engagement with corporate social responsibility (CSR) activities on consumers' purchasing intention has been observed (Al-Haddad et al, 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 93%